Bioremediation of chlorinated solvents and diesel soils - Huismann,SS; Peterson,MA; Jardine,RJ (1995)
The United States Army, the Tennessee Valley Authority (TVA) and ENSR collaborated to perform an innovative enhanced bioremediation project at Fort Gillem in Atlanta, Georgia. The objective of the project was to remediate six hundred cubic yards of soil affected by a mixture of chlorinated compounds and petroleum hydrocarbons which posed a threat to uppermost groundwater and private drinking water wells. ENSR completed a demonstration project in which the effects of bioremediation on both chlorinated compounds and petroleum hydrocarbons were measured. In addition, ENSR also monitored bioremediation through periodic sampling of air, soil, and water.